Pressure-dependent magnetism of the Kitaev candidate Li2RhO3 - Bin Shen; Efrain Insuasti Pazmino; Ramesh Dhakal; Friedrich Freund; Philipp Gegenwart; Stephen M. Winter; Alexander A. Tsirlin (npj Quantum Materials)
Abstract We use magnetization measurements under pressure along with ab initio and cluster many-body calculations to investigate magnetism of the Kitaev candidate Li2RhO3. Hydrostatic compression leads to a decrease in the magnitude of the nearest-neighbor ferromagnetic Kitaev coupling K 1 and the corresponding increase in the off-diagonal anisotropy Γ1, whereas the experimental Curie-Weiss temperature changes from negative to positive with the slope of +40 K/GPa. On the other hand, spin freezing persists up to at least 3.46 GPa with the almost constant freezing temperature of 5 K that does not follow the large changes in the exchange couplings and indicates the likely extrinsic origin of spin freezing. Magnetic frustration in Li2RhO3 is mainly related to the interplay between ferromagnetic K 1 and antiferromagnetic Γ1, along with the weakness of the third-neighbor coupling J 3 that would otherwise stabilize zigzag order. The small J 3 distinguishes Li2RhO3 from other Kitaev candidates.